Pkm Remaja Karang Taruna Pengenalan Flutter Dalam Membangun Aplikasi Mobile Jatiranggon Bekasi - Nasrullah Isnain; Han sulaiman; Julizal Julizal (BADAN PENERBIT STIEPARI PRESS, 2023)
This community service aims to implement Android-based learning by using Flutter to make youth youth organizations RT 01 RW 05 get good results. Lots of teenagers. For this reason, we provide the best solution in utilizing face-to-face meetings which must be carried out effectively, efficiently, and easily accessible to the students who are mentored, especially for Karang Taruna Youth. By utilizing applications that are in accordance with the needs of supervisors and students not closing teaching and learning activities in Flutter based on Android, namely providing an understanding in making android applications, ready or not, the Flutter method needs to be carried out according to their abilities so that the teaching and learning process continues and the foundation needs to prepare children under his guidance to be creative, smart, and innovative..